2008
DOI: 10.1111/j.1440-1681.2008.04971.x
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar–arterial Oxygen Gradient, Pneumonia Severity Index and Outcomes in Patients Hospitalized With Community Acquired Pneumonia

Abstract: The alveolar-arterial oxygen gradient (DeltaA-a) provides a useful assessment of ventilation/perfusion (V/Q) abnormalities. The objectives of the present study were to: (i) examine the correlation between the DeltaA-a and the pneumonia severity index (PSI); and (ii) determine whether these measures were comparable in predicting clinical outcomes. The present study was conducted at a 750-bed teaching hospital. It examined a retrospective cohort of 255 patients with community acquired pneumonia (CAP) over a 2 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…Fisher's exact test was used to evaluate statistical significance of dichotomised categorical data and the odds ratio (OR) was used to evaluate the magnitude of effect. The cut-off previously established [7] for high-risk CAP (≥89 mmHg) was used to dichotomise this variable; receiver-operating characteristic (ROC) curve analysis was used to establish a cut-off for cTnI. For statistical evaluation, α was set at 0.05; p-values (two-sided) < 0.05 were considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fisher's exact test was used to evaluate statistical significance of dichotomised categorical data and the odds ratio (OR) was used to evaluate the magnitude of effect. The cut-off previously established [7] for high-risk CAP (≥89 mmHg) was used to dichotomise this variable; receiver-operating characteristic (ROC) curve analysis was used to establish a cut-off for cTnI. For statistical evaluation, α was set at 0.05; p-values (two-sided) < 0.05 were considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…The dynamic range of this assay is 0.01-100 ng/ml, however samples may be further diluted to estimate concentrations 10-fold higher. The values for A-a were calculated as previously described [7].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[112] Hence, CURB-65 can be supplemented with clinical judgment and/or pulse oximetry. [113117] In a meta-analysis of 397,875 patients, CRB-65 performed well in stratifying the severity of pneumonia and the resultant 30-day mortality in hospital settings, while it appeared to overpredict the probability of 30-day mortality across all strata of predicted risk in community settings. [118] CRB-65 had an acceptable ability to classify mortality risk in the age group >65 years; patients with CRB-65 ≤1 had a relatively small mortality rate, which suggested that they could be managed as outpatients.…”
Section: Community-acquired Pneumoniamentioning
confidence: 99%